SEGMENT 10 SEQUENCE BASED MOLECULAR CHARACTERIZATION OF BLUETONGUE VIRUS OF INDIAN ORIGIN - Prasad, Minakshi; Ranjan, Koushlesh; Prasad, Gaya (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Bluetongue disease (BT) is an infectious but non-contagious viral disease of wild and domestic ruminants. The complete genome of BTV isolate K31-08/ABT/HSR was sequenced using Ion-Torrent PGM system. The sequence data were denovo assembled and contig sequences were prepared with reference to known sequences from GenBank. The segment 10 based analysis segregates BTV in five distinct topotypes. The segment 10 of K31-08/ABT/HSR isolate showed maximum identity of >99/99%, nucleotide/amino acid with BTV 16 isolates from India and placed under eastern topotype viruses from India and several other countries. The clustering of BTV isolates from different geographical regions into same group indicated the spatial spread of the segment 10 through introduction of new genes via trade or illegal live vaccine or reassortment. It also indicates the common origin of segment 10 irrespective of BTV serotype. The effect of reassortment and genetic drift on BTV can be predicted using complete genome sequencing technique.
Keywords: Bluetongue virus; serotype; topotype; segment 10; RT-PCR